2017
DOI: 10.17219/acem/31186
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of curcumin and deferoxamine in experimental endometriosis

Abstract: Background. Endometriosis is one of the most common chronic gynecological diseases. Objectives. The aim of the study was to examine the effects of curcumin and/or deferoxamine on cell proliferation in a rat model of endometriosis. Material and methods. Thirty female 12-week-old albino Wistar rats, weighing 200-250 g, were used in this study. All the rats underwent ovariectomy and 0.1-mg β-estradiol 17-valerate pellets were placed intraperitoneally. An experimental model of endometriosis was created in all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, curcumin inhibited cell proliferation and caused cell apoptosis, and reduced inflammation through suppression of inflammatory cytokines expression. Treatment with curcumin alone and/or in combination with deferoxamine contributed to a reduction in implant size and cell proliferation in a rat endometriosis model [ 105 ]. Curcumin also induced apoptosis through a cytochrome-C-mediated mitochondrial pathway and in a p53 (a tumor suppressor gene)-dependent and -independent manner in a mouse model of endometriosis [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, curcumin inhibited cell proliferation and caused cell apoptosis, and reduced inflammation through suppression of inflammatory cytokines expression. Treatment with curcumin alone and/or in combination with deferoxamine contributed to a reduction in implant size and cell proliferation in a rat endometriosis model [ 105 ]. Curcumin also induced apoptosis through a cytochrome-C-mediated mitochondrial pathway and in a p53 (a tumor suppressor gene)-dependent and -independent manner in a mouse model of endometriosis [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 illustrates the proposed effect of curcumin on the inflammatory and apoptotic pathways in endometriosis. activity by 50%, 70% and 80% and the synthesis of MMP-9 decrease significantly by 60%, 70% and 90%, respectively In the therapeutic model: -Curcumin decreased the secreted MMP-9 activity by 45% and 85%, inhibited TNF-α and elevated TIMP-1 -Curcumin decreased lipid peroxidation and protein carbonylation [78] Autotransplantation of endometrium tissue during oestrus stage in Wistar rats 50, 100 and 150 mg/kg/d curcumin 0.5% sodium carboxymethyl cellulose solution (vehicle) Intragastric injection Daily for 4 weeks -Hyperplasia in ectopic tissue was halted -Disappearance of the ectopic gland tissue with the narrowed lumen and sparse cells -Microvessel density (MVD) was higher in ectopic endometrium -In eutopic endometrium, all treated groups showed no significant difference compared with the normal group -Eutopic and ectopic endometrium expression of VEGF protein in the model rat group was higher than in the normal group [79] Dimethyl sulfoxide (DMSO) autotransplantation of endometrium tissue from the right horn of the uterus and placed be-tween the peritoneum and muscle of ovariectomised albino Wistar rats DMSO as vehicle 100 mg/kg of curcumin 100 mg/kg of deferoxamine + curcumin Intragastric Group A: Water for injection daily for 3 days and DMSO Group B: Curcumin Group C: Deferoxamine at 6 h interval for 3 days and curcumin Daily for 20 days -Endometriotic-like implant sizes were significantly reduced in groups B and C compared with group A (control) -Stroma and glands with surrounding fibrous connective tissue were present and well vascularised in the ectopic endometrium -Cytokeratin-7 antibodies displayed an immunoreactivity in glandular epithelial cells of both eutopic and ectopic endometrium -Blood iron levels were not significantly different between the treatment groups according to atomic absorption spectrophotometry results [80] Hetero-transplant of the endometrium of the uterine horn of donor mice into the peritoneal cavity containing subcutaneous implant of oestradiol-17β pellet of recipient BALB/c mice 48 mg/kg/day of curcumin Intraperitoneal injection Daily for 3 days -No changes were seen in MMP-2 activity for the first 24 h -Both synthesised and secreted proMMP-2 activity were increased after 48 h -Curcumin suppressed the pro-MMP-2 activity, and progression of endometriosis was delayed -Activation of pro-MMP-2 was inhibited; hence, MMP-2 activity was halted by curcumin during the early stage of endometriosis -Upregulation of TIMP-2 inhibited MMP-2 activity during regression of endometriosis by curcumin -MT1MMP regulated MMP-2 activity, as confirmed by immunoblotting. Curcumin downregulated MT1MMP expression by 40% compared with the normal sample -Complex formation between MMP-2 and TIMP-2 was significantly increased in the curcumin-treated group, which inhibited MMP-2 activity and endometriosis progression [81] Abbreviations: TNF-α: tumor necrosis factor α; MMP: matrix metalloproteinase; TIMP: tissue inhibitor matrix metalloproteinase; NF-κB: nuclear factor κ-light-chain-enhancer of activated B; MVD: microvessel density; DMSO: dimethyl sulfoxide; VEGF: vascular endothelial growth factor; Cyt-c: cytochrome C; Bax: BCL2 associated X; TAC: total antioxidant capacity; MT1MMP: membrane type-1 matrix metalloproteinase; MAPK: mitogen-activated protein kinase.…”
Section: Effect Of Curcumin On Endometriosismentioning
confidence: 91%
“…All studies employing animal experimental models of endometriosis showed a regression in the size of ectopic endometrium implants with F I G U R E 1 Flow diagram of the process of selection of the articles curcumin treatment (Swarnakar & Paul, 2009), (Zhang et al, 2011), (Jana et al, 2012), (Kizilay et al, 2017), (Jelodar & Azimifar, 2019). The reduction resulting from local decrement of VEGF expression and microvessel density (MVD) was proportional to curcumin dose administered to rats.…”
Section: Animal Studiesmentioning
confidence: 99%
“…While the effect of quercetin in signaling pathways associated to cell proliferation (Park et al, 2018) and of resveratrol in IGF-1, HGF, and MTA1 expression is documented (Arablou et al, 2019), (Kong et al, 2020), for curcumin, only the effect in cell cycle arrest was described (Cao et al, 2017), (Zhang et al, 2013). Intervention on apoptotic vias and regression of endometriotic implants was demonstrated for the three compounds (Cao et al, 2017), (Swarnakar & Paul, 2009), (Zhang et al, 2011), (Jana et al, 2012), (Kizilay et al, 2017), (Park et al, 2018), (Taguchi et al, 2016), (Khazaei et al, 2020), (Kolahdouz-Mohammadi et al, 2020), (Rudzitis-Auth et al, 2013), (Ergeno glu et al, 2013), (Yavuz et al, 2014), (Cenksoy et al, 2014), (Tekin et al, 2015), (Bahrami et al, 2021), (Wang et al, 2021), (Ricci et al, 2013), (Bruner-Tran et al, 2011), (Kong et al, 2020), (Chen et al, 2021).…”
Section: Risk Of Bias Of Studiesmentioning
confidence: 99%